The Effect of Surface Color on the Absorption of Solar Radiation - Paminto, Joko; Fianti, Fianti; Yulianti, Ian (Physics Communication, 2021)
This research was conducted to verify the effect of the color of the object's surface on the absorption of solar radiation. The purpose of this study was to determine how the effect of surface color on the absorption of solar radiation. The activity used an acrylic box covered by stickers of various colors, placed under the sun, then measured the heat absorption of the covered liquid using a digital thermometer. The results showed that there was an effect of the color of the object's surface on the absorption of solar radiation which was indicated by the difference in the temperature increase of the covered liquid. The hypothesis can be accepted at the 95% confidence level. The order surface color of objects on the absorption level of solar heat is black, green, red, purple, yellow, pink, blue and white from the highest to the lowest.